PERCEFAL: instrumento de avaliação da identificação de contrastes fonológicos - Berti, Larissa Cristina (Academia Brasileira de Audiologia, 2017)
ABSTRACTIntroduction: There is a growing interest of researchers in instruments designed for assessment of speech perception.Purpose: To develop an instrument to perceptual identification of phonemic contrasts in the Brazilian Portuguese for children over 4 years of age.Methods: The construction of the instrument involved four procedures: a) design of the experimental task; b) stimuli selection which constituted the instrument; c) operationalization of the test; and d) establishing the analysis criteria. It was used a computer attached to a headphone and PERCEVAL software.Results: The proposed instrument comprises a subset of four experiments that evaluate separately the identification of contrasts between vowel segments and between stops consonant segments, fricative and sonorant consonant segments. The test presents includes three stages: word recognition stage, training stage and testing stage, with an approximate 15-minute overall duration. The analysis of children's auditory perceptual performance is carried out based on three criteria: accuracy, reaction time and pattern of phonic contrasts identification, being recorded following a specific protocol.Conclusion: Studies that have used the PERCEFAL in their methodology have reported a low percentage of non-response by children (between 2 and 5%), which indicates that the task is appropriate for its purpose. It is encouraged the use of the instrument in different regions of the country in order to inquire not only its applicability, due to the existing linguistic diversity in the country; but also, to determine its sensitivity and specificity.

RESUMOIntrodução Verifica-se um crescente interesse de pesquisadores por instrumentos designados para avaliação da percepção da fala.Objetivo Construir um instrumento de identificação perceptual de contrastes fônicos do Português Brasileiro para crianças a partir de 4 anos de idade.Métodos A construção do instrumento envolveu quatro procedimentos: a) delineamento da tarefa experimental; b) seleção dos estímulos que constituíram o instrumento; c) operacionalização do teste; d) estabelecimento dos critérios de análise. Foi utilizado um computador acoplado a um fone de ouvidos e o software PERCEVAL.Resultados O instrumento proposto compreende um subconjunto de quatro experimentos que avaliam, separadamente, a identificação de contrastes entre segmentos vocálicos e entre segmentos consonantais oclusivos, fricativos e soantes. O teste envolve três etapas: fase de reconhecimento de palavras, fase treino e fase teste, com duração total de 15 minutos, aproximadamente. A análise do desempenho perceptivoauditivo das crianças é feita a partir de três critérios: acurácia, tempo de reação e padrão de identificação dos contrastes fônicos, sendo registrada em um protocolo específico.Conclusão Estudos que têm utilizado o PERCEFAL em sua metodologia reportam baixa porcentagem de não resposta por parte das crianças (entre 2% e 5%), o que indica que a tarefa mostra-se apropriada para a sua finalidade. Encoraja-se o uso do instrumento nas diversas regiões do país, para averiguar, não somente sua aplicabilidade, dada à diversidade linguística do país, como também para verificar sua sensibilidade e especificidade.
PERCEFAL: an instrument to assess identification of phonological contrasts in Brazilian Portuguese
Keywords: Speech perception; Phonetic; Child; Percepção da fala; Fonética; Criança